Epidemiology of violence against adolescents in Brazil: Data analysis of the violence and accident surveillance system - Salazar López, María Esther (2021)
Objective: To describe the characteristics of violence against adolescents in Brazil reported from the Violence and Accident Surveillance System (VIVA). Methods: A descriptive study, based on data from the VIVA, Brazil, from2009 to 2016. The variables analyzed were age, gender, race, place of occurrence, bond between the aggressor and the victim, and suspected of alcohol use in cases of physical, psychological/moral and sexual violence. Descriptive statistics and tends proportion test with STATA were used. Results: The prevalence rate of physical violence in the 15-19 years age bracket reached 104.4 per 100,000 cases, and the prevalence of sexual violence in the 10-14 years age bracket was 38.5 per 100,000 cases. Sexual violence reached 52.0 per 100,000 cases in girls, compared to 4.5 per 100,000 in boys. There was a significant upward trend in physical violence in the 15-19 years age bracket, and in sexual violence in the 10-14 years age bracket. Both types of violence affecting more frequently brown and indigenous races, and happening at the victim’s home, with the perpetrator being the adolescent’s boyfriend. In cases of sexual violence, the suspicion of alcohol use by the aggressor has grown. The percentage change in physical and psychological violence increased by more than 400%. Conclusions: Regardless of the type of violence, there was an increase in the eight years. Notifications of physical and sexual violence were more frequent, affecting mainly girls, in their residence, being a friend/acquaintance or boyfriend of the victim the main aggressors.